Faktor Yang Berhubungan Dengan Kejadian Ulkus Kornea : Literatur Review - Laras Pratiwi, Astari; Suharmanto, Suharmanto; Taolin, Alberto (Medula, 2025)
Corneal ulcer is a pathological condition in the form of a lesion or defect caused by the loss of tissue discontinuity accompanied by infiltration, which can occur in the cornea, from the epithelium to the stroma. This literature review aims to describe the factors associated with the occurrence of corneal ulcers. This literature review describes the factors associated with the occurrence of corneal ulcers. Researchers use articles from Google Scholar and PubMed. The articles used are articles from the last 10 years from 2015-2025. Researchers use the keywords "corneal ulcer" and "factors". The articles obtained were 39 articles and 10 articles met the requirements. Researchers made a resume of the research results and interpreted and concluded from the selected articles. Corneal ulcers can be caused by various risk factors, both infectious and non-infectious. Unhygienic or prolonged use of contact lenses, viral infections such as herpes simplex, dry eye syndrome, eyelid disorders (such as entropion or trichiasis), use of steroid eye drops without medical supervision, and trauma or injury to the eye are the main causes. In addition, people with diabetes mellitus and those with a history of eye diseases such as blepharitis are also more susceptible to corneal ulcers.